Structural assessment of iron tie rods based on numerical modelling and experimental observations in Milan Cathedral. (1st March 2020) - Angjeliu, Grigor; Coronelli, Dario; Cardani, Giuliana; Boothby, Thomas
Highlights: Use of an advanced numerical model for the interpretation of the experimentally measured tension force in iron ties. The investigation of the iron ties rods is directly related to the statics and the safety of the structural system. Load history has important effects on the tension force developed in the iron ties. Prediction of the iron tie rods tension state during replacement or maintenance operations. Abstract: Iron ties contribute to the stability of structural systems having vaults and arches. The axial force in the iron ties is not easily to be measured but this knowledge is important for assessing the safety of these members. In the case of breakage of iron tie rods, the assessment study needs to understand the causes of the failures. Experimental data are collected, and models are used for their interpretation. The aim of this paper is to propose a new integrated experimental and numerical approach for the structural analysis of tie rod tensions in historical buildings. The study considers an application at Milan Cathedral, where recently some iron tie failures were observed. The collected data taken into account are: (a) Point cloud measurement of the geometry (b) Understanding of construction phases, (c) Soil-settlement measurement in the last 50 years, (d) Experimental measurement of the iron ties axial force, and (e) Documentation of damage and iron tie failures in the last century. It is here proposed to use an advanced numerical model for simulating, interpreting and predicting the measured response of the iron ties. The finite element numerical model includes detailed geometry of elements, material properties of masonry based on texture observations and iron ties modelling. The paper shows how the actual structural configuration, the choices on material properties, the consideration of construction stages or load history and soil settlements affect the tension state in the iron ties. In particular, it is demonstrated through the carried-out analysis the possibility to correlate the tension force in the ties with soil settlements. Finally, the developed numerical model can be used also during practical maintenance operations of iron tie replacement, by predicting the stressed state, the possible lateral displacements of the pier and the associated structural safety.